Perinatal Outcomes and Risk Factors for Preterm Birth in Twin Pregnancies in a Chinese Population: A Multi-center Retrospective Study - Li, Sijian; Gao, Jinsong; Liu, Juntao; Hu, Jing; Chen, Xiaoxu; He, Jing; Tang, Yabing; Liu, Xinghui; Cao, Yinli (Frontiers in Medicine, 2021)
Background: Twin pregnancies are associated with an increased risk of adverse maternal and neonatal outcomes, mainly owing to prematurity. Few studies have evaluated the risk factors for preterm birth (PTB) in Chinese population. The objective of this study is to present the short-term maternal-neonatal outcomes, investigating the potential risk factors associated with preterm birth in Chinese twin pregnancies. Methods: A multi-center retrospective study of women pregnant with twins ≥28 weeks of gestation was conducted. Maternal and neonatal outcomes were analyzed. Logistic regression was used to identify potential risk factors for PTB before 37, 34, and 32 weeks, respectively. Results: A total of 3288 twin pregnancies and 6576 neonates were included in 99585 pregnancies. The rate of twin pregnancy was 3.3%, while the PTB rate before 37, 34, and 32 weeks among this population were 62.1, 18.8, and 10.4%, respectively. Logistic regression revealed that monochorionicity (Odds ratio [OR] 3.028, 95% confident interval [CI] 2.489–3.683, P < 0.001), gestational weight gain (GWG) less than 10kg (OR 2.285, 95% CI 1.563–3.339, P < 0.001) and GWG between 10 and 15kg (OR 1.478, 95% CI 1.188–1.839, P < 0.001), preeclampsia (PE) (OR 3.067, 95% CI 2.142-4.390, P < 0.001), and intrahepatic cholestasis of pregnancy (ICP) (OR 3.122, 95% CI 2.121–4.596, P < 0.001) were the risk factors for PTB before 37 weeks. Monochorionicity (OR 2.865, 95% CI 2.344–3.501, P < 0.001), age < 25 years (OR 1.888, 95% CI 1.307–2.728, P = 0.001), and GWG less than 10kg (OR 3.100, 95% CI 2.198–4.372, P < 0.001) were risk factors for PTB before 34 weeks. Monochorionicity (OR 2.566, 95% CI 1.991–3.307, P < 0.001), age younger than 25 years (OR 1.964, 95% CI 1.265–3.048, P = 0.003), and GWG less than 10kg (OR 4.319, 95% CI 2.931–6.364, P < 0.001) were the risk factors for PTB before 32 weeks. Conclusions: Monochorionicity and GWG less than 10kg were two major risk factors for PTB before 32, 34, and 37 weeks, whereas maternal age, PE, and ICP were also risk factors for PTB in specific gestational age.